Use of the prioritization matrix to enhance triage algorithms in clinical decision support software. - North F; Varkey P (American Journal of Medical Quality, 2010)
Clinical decision support (CDS) software requires regular maintenance and development. CDS software can be very complex and can have several different performance parameters that need to be considered in development and maintenance cycles. Stakeholders in management and software development need a shared and mutually agreed on framework to prioritize the development and maintenance of CDS software. The prioritization matrix, a quality improvement tool, was used to prioritize triage algorithms at Ask Mayo Clinic, a national triage call center. Key elements used in the priority matrix were the frequency of algorithm use, potential safety impact of the algorithm, algorithm length, overall agreement between software recommendation and triage nurse, and asymmetry of nurse overrides of the software recommendation. This methodology also bridges the language gap between software developers and management and gives management the ability to customize how software maintenance and development cycles are prioritized.